1998
DOI: 10.2307/1370269
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Forage-Fish Schools by Murrelets and Tufted Puffins in Prince William Sound, Alaska

Abstract: We collected hydroacoustic and bird-observation data simultaneously along transects in three areas in Prince William Sound, Alaska, 21 July-l 1 August 1995. The probability of the association of fish schools with Marbled Murrelets (Brachyramphus marmoratus) and Tufted Puffins (Fratercula cirrhata) was determined through the use of resource selection functions based on logistic regression. Mean (5 SD) group sizes were small for both species, 1.7 2 1.1 and 1.2 k 0.7 for Marbled Murrelets and Tufted Puffins, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…4A), which does support the 'stay on prey patch' hypothesis. Ostrand et al (1998) also found a positive relationship between marbled murrelet and prey distribution in Prince William Sound, Alaska, where birds selected small, dense fish schools in shallow waters that were associated with stratified water. The oceanography of Prince William Sound has fewer potential prey-aggregating mechanisms than the highly dynamic California Current, and may be similar to California waters when upwelling is low or relaxed.…”
Section: Nested Effects Of Spatial Scale On Habitat Selectionmentioning
confidence: 74%
See 1 more Smart Citation
“…4A), which does support the 'stay on prey patch' hypothesis. Ostrand et al (1998) also found a positive relationship between marbled murrelet and prey distribution in Prince William Sound, Alaska, where birds selected small, dense fish schools in shallow waters that were associated with stratified water. The oceanography of Prince William Sound has fewer potential prey-aggregating mechanisms than the highly dynamic California Current, and may be similar to California waters when upwelling is low or relaxed.…”
Section: Nested Effects Of Spatial Scale On Habitat Selectionmentioning
confidence: 74%
“…However, the spatial and temporal resolution of previous studies limits inferences regarding the dynamics of murrelet habitat selection under both short-term (weekly) and long-term (annual) changes in prey availability, ocean conditions, and spatial scale (Ostrand et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Only the tufted puffin, however, exhibited near complete breeding failure in the warmest years, suggesting a sensitivity that surpassed that of the other species. Puffins tend to be diurnal foragers that provision young multiple times per day, a strategy that restricts parental foraging range (Ostrand et al 1998). In contrast, each rhinoceros auklet parent provisions its young at most once per night (max.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological requirements for survival, or time to starvation (Horne & Schneider 1994), is likely the most important determinant of the tracking scale of seabirds due to their high metabolic rates and low energy reserves compared to other marine animals (Gabrielsen 1994, Gaston & Jones 1998. Physical characteristics of the foraging environment of seabirds, such as hydrographic regimes, combined with prey behaviour, influence the spatial scale and density of prey patchiness (Mehlum et al 1996, Ostrand et al 1998) and the stability of prey patches in space and time (Cairns & Schneider 1990, Hunt & Harrison 1990, Irons 1998. These factors in turn affect predator tracking scales (Rose & Leggett 1990, Davoren 2000.…”
Section: Introductionmentioning
confidence: 99%